Chromosomal analysis of blastocysts from balanced chromosomal rearrangement carriers. Issue 4 (April 2016) - Gui, Baoheng; Yao, Zhongyuan; Li, Yanping; Liu, Donge; Liu, Nenghui; Xia, Yan; Huang, Yanru; Mei, Libin; Ma, Ruiyu; Lu, Sijia; Liang, Desheng; Wu, Lingqian
Abstract : Balanced chromosomal rearrangements (CRs) are among the most common genetic abnormalities in humans. In the present study, we have investigated the degree of consistency between the chromosomal composition of the blastocyst inner cell mass (ICM) and trophectoderm (TE) in carriers with balanced CR, which has not been previously addressed. As a secondary aim, we have also evaluated the validity of cleavage-stage preimplantation genetic diagnosis (PGD) based on fluorescence in situ hybridization (FISH) of blastocysts from CR carriers. Blastocyst ICM and TE were screened for chromosomal aneuploidy and imbalance of CR-associated chromosomes based on whole-genome copy number variation analysis by low-coverage next-generation sequencing (NGS) following single-cell whole-genome amplification by multiple annealing and looping-based amplification cycling. The NGS results were analyzed without knowledge of cleavage-stage FISH results. NGS results for blastocyst ICM and TE from CR carriers were 86.49% (32/37) consistent. Of the 1702 (37×46) chromosomes examined, 99.47% (1693/1702) showed consistency. However, only 40.0% (18/45) of all embryos had consistent results for chromosomes involved in CR, as determined by blastocyst NGS and cleavage-stage FISH. Of the 85 CR-affected chromosomes analyzed by FISH, 37.65% (32/85) were incongruous with NGS results, with 87.5% (28/32) showing imbalanced composition by FISH but balanced composition by NGS. These results indicate that chromosomal composition of blastocyst ICM and TE in balanced CR carriers is highly consistent, and that PGD based on cleavage-stage FISH is inaccurate; therefore, using blastocyst TE biopsies for NGS-based PGD is recommended for identifying chromosomal imbalance in embryos from balanced CR carriers.